2015
DOI: 10.12659/msm.892554
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Long-Term Post-Stroke Cognitive Impairment in Young Adult Ischemic Stroke

Abstract: BackgroundPost-stroke cognitive impairment is common and a decisive prognostic factor. However, few studies have reported on post-stroke cognition in young adults, especially long-term cognition. This study was designed to investigate the influence of baseline factors, treatments, and functional outcome on the long-term cognitive outcome in young adults with ischemic stroke.Material/MethodsConsecutive patients aged 18–45 years between January 1, 2006 and December 31, 2010, with a first-ever ischemic stroke, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 29 publications
1
24
1
Order By: Relevance
“…Our findings about demographic factors (age and sex) and discharge disposition contradicted with previously reported results [ 21 , 39 , 40 ]. A previous literature review found that numerous variables were associated with outcomes after inpatient rehabilitation [ 39 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings about demographic factors (age and sex) and discharge disposition contradicted with previously reported results [ 21 , 39 , 40 ]. A previous literature review found that numerous variables were associated with outcomes after inpatient rehabilitation [ 39 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In other words, neurological deficit was a major contributor to post-stroke disability, the result is consistent with the findings of previous studies. 24,25 In this study, we also found that cognitive function was strongly associated with post-stroke disability in the third year of follow-up, the result is consistent with the conclusion drawn by Huang et al 26 Cognitive impairment stroke patients may have attention deficit, leading to a decline in understanding and social adaptability, and resulting in negative outcomes in neural functional recovery.…”
Section: Discussionsupporting
confidence: 92%
“… 38 In general, hypertension does not exist alone; it is always accompanied by other risk factors, such as metabolic risks 39 , 40 or stroke-related factors. 41 , 42 Future research should focus on the interaction of multiple risk factors with a longer follow-up period.…”
Section: Discussionmentioning
confidence: 99%